Occupational exposures and incidence of chronic bronchitis and related symptoms over two decades: the European Community Respiratory Health Survey. Issue 4 (30th January 2019) - Lytras, Theodore; Kogevinas, Manolis; Kromhout, Hans; Carsin, Anne-Elie; Antó, Josep Maria; Bentouhami, Hayat; Weyler, Joost; Heinrich, Joachim; Nowak, Dennis; Urrutia, Isabel; Martínez-Moratalla, Jesús; Gullón, José Antonio; et al.
Abstract : Objectives: Chronic bronchitis (CB) is an important chronic obstructive pulmonary disease (COPD)-related phenotype, with distinct clinical features and prognostic implications. Occupational exposures have been previously associated with increased risk of CB but few studies have examined this association prospectively using objective exposure assessment. We examined the effect of occupational exposures on CB incidence in the European Community Respiratory Health Survey. Methods: Population samples aged 20–44 were randomly selected in 1991–1993, and followed up twice over 20 years. Participants without chronic cough or phlegm at baseline were analysed. Coded job histories during follow-up were linked to the ALOHA Job Exposure Matrix, generating occupational exposure estimates to 12 categories of chemical agents. Their association with CB incidence over both follow-ups was examined with Poisson models using generalised estimating equations. Results: 8794 participants fulfilled the inclusion criteria, contributing 13 185 observations. Only participants exposed to metals had a higher incidence of CB (relative risk (RR) 1.70, 95% CI 1.16 to 2.50) compared with non-exposed to metals. Mineral dust exposure increased the incidence of chronic phlegm (RR 1.72, 95% CI 1.43 to 2.06). Incidence of chronic phlegm was increased in men exposed to gases/fumes and to solvents and in women exposed to pesticides. Conclusions: Occupational exposures are associated with chronic phlegm and CB, and the evidence is strongest for metals and mineral dust exposure. The observed differences between men and women warrant further investigation.